1992
DOI: 10.1007/bf02446968
|View full text |Cite
|
Sign up to set email alerts
|

Potential distribution and single-fibre action potentials in a radially bounded muscle model

Abstract: In modelling the electrical behaviour of muscle tissue, we used to employ a frequency-dependent volume conductor network model, which was infinitely extended in all directions. Equations in this model could be solved using a finite-difference approach. The most important restriction of this model was the fact that no boundary effects could be incorporated. Analytical models of muscle tissue normally do not have this disadvantage, but in those models the microscopic structure of muscle tissue cannot be taken in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
19
0

Year Published

1996
1996
2006
2006

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 18 publications
1
19
0
Order By: Relevance
“…These models have been predominantly based on analytical solutions for muscle fibers located in either finite or infinite volume conductors [1]- [6]. Analytical models, however, are limited to simple cylindrical or elliptical geometries and become increasingly difficult to handle as additional layers are incorporated.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These models have been predominantly based on analytical solutions for muscle fibers located in either finite or infinite volume conductors [1]- [6]. Analytical models, however, are limited to simple cylindrical or elliptical geometries and become increasingly difficult to handle as additional layers are incorporated.…”
mentioning
confidence: 99%
“…To date, a limited number of models have considered the finite nature of the volume conductor in which the muscle fibers lie [3]- [6], [11]. Of these, only the models of Gootzen et al, [3] and Roeleveld et al, [5] have incorporated multiple layers of fat and skin tissue, although fat and skin layers have been included in a recent hemi-space model for planar geometries [12].…”
mentioning
confidence: 99%
“…Some studies have considered cylindrical volumes embedded in infinite volume conductors [14], [15]. Only a few studies have considered the finite dimensions of a cylindrical volume conductor [16]- [20]. These studies have shown that the boundary can have a significant impact on single fiber action potentials.…”
mentioning
confidence: 99%
“…This could significantly affect the amplitude, as well as the phase and shape, of the EMG signal. Although some investigators have considered the effects of capacitance near the source [10], [20], [26], [27], none have included the permittivity of the tissue as a whole. A full electromagnetics model is necessary to quantify these effects and determine their significance.…”
mentioning
confidence: 99%
See 1 more Smart Citation